Bivalirudin vs. heparin on a background of ticagrelor and aspirin in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention: A multicenter prospective cohort study - Yu, Xiao-Fan; Chen, Hong-Wu; Xu, Jie; Xu, Qi-Zhi; Zhang, Xiao-Hong; Li, Bin-Bin; Xu, Bang-Long; Ma, Li-Kun (Frontiers in Cardiovascular Medicine, 2022)
Objective Current guidelines recommend potent P2Y12 inhibitors such as ticagrelor over clopidogrel as part of the dual antiplatelet therapy (DAPT) after ST-segment elevation myocardial infarction (STEMI), irrespective of final management strategy. The aim of this multicenter prospective cohort study was to examine the efficacy and safety of bivalirudin with background ticagrelor and aspirin therapy in patients with STEMI undergoing primary percutaneous coronary intervention (PPCI). Methods A total of 800 patients with STEMI who were undergoing PPCI and receiving treatment with aspirin and ticagrelor from three Hospitals between April 2019 and September 2021 were included in this study. The patients were assigned, according to the perioperative anticoagulant, to the bivalirudin group (n = 456) or the heparin group (n = 344). In this study, the primary endpoint was 30-day net adverse clinical events (NACEs), a composite of major adverse cardiac or cerebral events (MACCEs, a composite of cardiac death, recurrent myocardial infarction, ischemia-driven target vessel revascularization, or stroke), or any bleeding as defined by the Bleeding Academic Research Consortium (BARC) definition (grades 1–5). Results The patients were followed up for 30 days after PPCI. The incidence of NACE was significantly lower in the bivalirudin group than in the heparin group (11.2 vs. 16.0%, P = 0.042), and this significance was mainly a consequence of the reduction in BARC 1 bleeding events in the bivalirudin group compared to the heparin group (3.2 vs. 7.1%, P = 0.010). Results from multivariate Cox regression analysis showed that bivalirudin significantly reduced 30-day NACE (HR: 0.676, 95% CI: 0.462–0.990, P = 0.042) and BARC1 bleeding events (HR: 0.429, 95% CI: 0.222–0.830, P = 0.010). No significant between-group differences were observed for MACCE, all-cause mortality, cardiac death, recurrent myocardial infarction, stroke, target vessel revascularization, stent thrombosis, and BARC2-5 bleeding events at 30 days. Conclusion In patients with STEMI who were undergoing primary PCI and receiving treatment with aspirin and ticagrelor, bivalirudin was associated with decreased rates in NACE and minimal bleeding events without significant differences in the rates of MACCE or stent thrombosis when compared with heparin. Nevertheless, large randomized trials are warranted to confirm these observations. Clinical trial registration The trial was registered at the Chinese Clinical Trial Registry (ChiCTR, http://www.chictr.org.cn; identifier [ChiCTR1900022529]). Registered on 15 April 2019. Registration title: Effect of bivalirudin combined with ticagrelor in patients with ST-segment elevation myocardial infarction during primary percutaneous coronary intervention.